2015
DOI: 10.1097/igc.0000000000000443
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Survival of Gynecologic Sarcomas in England

Abstract: Gynecologic sarcoma incidence rates have varied little since 1993, whereas survival has improved significantly. These results are consistent with previously published small series and case studies, and provide a more complete picture of gynecologic sarcoma incidence and survival patterns in England.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 27 publications
3
29
1
Order By: Relevance
“…These findings are in line with data from England reported by Francis et al, 8 who found an incidence for GS of 8.6 in 1 million women diagnosed between 2001 and 2008. Most GS was located in the uterus (87.9%), which was also similar to the proportion reported from Francis et al 8 (83%).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These findings are in line with data from England reported by Francis et al, 8 who found an incidence for GS of 8.6 in 1 million women diagnosed between 2001 and 2008. Most GS was located in the uterus (87.9%), which was also similar to the proportion reported from Francis et al 8 (83%).…”
Section: Discussionsupporting
confidence: 93%
“…9,12 Our 5-year relative survival rates for uterine (52.5%) and ovarian sarcoma (45.9%) were somewhat higher than those recently reported from England for the period of 2000 to 2004 (48% for uterine sarcoma and 42% for ovarian sarcoma). 8 However, lower survival rates for the United Kingdom have already been described for gynecological tumors in general compared with countries in Northern and Central Europe. 12 Although based on data dated back to the 1980s, similar relative 5-year survival rates were reported from Norway compared with those we found for LMS (46% vs 46.1%) but lower for ESS (73% vs 97.2%).…”
Section: Discussionmentioning
confidence: 99%
“…Leiomyosarcomas (LMS) account for 1% of all uterine cancers and 35-40% of all uterine sarcomas, and therefore are the most common gynaecological sarcomas (164,165). Although rapidly growing pelvic mass can be a sign of uterine sarcoma, Parker et al, in their series of patients undergoing hysterectomy for a rapidly growing uterus found only one LMS out of 371 women (166).…”
Section: Uterine Leiomyosarcomamentioning
confidence: 99%
“…Gynaecological sarcomas account for approximately 3% to 4% of all gynaecological malignancies and are associated with poor outcomes compared with gynaecological carcinomas [1]. Uterine sarcomas are approximately 83% of all gynaecological sarcomas.…”
Section: Introductionmentioning
confidence: 99%